A Method for the Immunohistochemical Identification and Localization of Osterix in Periosteum-Wrapped Constructs for Tissue Engineering of Bone. (July 2017) - McClellan, Phillip; Jacquet, Robin; Yu, Qing; Landis, William J.
A novel immunohistochemistry (IHC) approach has been developed to label and localize osterix, a bone-specific transcription factor, within formalin-fixed, paraffin-embedded, tissue-engineered constructs uniquely containing synthetic polymers and human periosteal tissue. Generally, such specimens consisting in part of polymeric materials and mineral are particularly difficult for IHC identification of proteins. Samples here were fabricated from human periosteum, electrospun poly-l -lactic acid (PLLA) nanofibers, and polycaprolactone/poly-l -lactic acid (PCL/PLLA, 75/25) scaffolds and harvested following 10 weeks of implantation in athymic mice. Heat-induced and protease-induced epitope retrieval methods from selected existing protocols were examined to identify osterix. All such protease-induced techniques were unsuccessful. Heat-induced retrieval gave positive results for osterix immunohistochemical staining in sodium citrate/EDTA/Tween 20 with high heat (120C) and pressure ( 30 psi) for 10 min, but the heat and pressure levels resulted in tissue damage and section delamination from slides that limited protocol effectiveness. Heat-induced epitope retrieval led to other osterix-positive staining results achieved with minimal impact on structural integrity of the tissue and polymers in sodium citrate/EDTA/Tween 20 buffer at 60C and normal pressure (14.5 psi) for 72 hr. The latter approach identified osterix-positive cells by IHC within periosteal tissue, layers of electrospun PLLA nanofibers, and underlying PCL/PLLA scaffolds of the tissue-engineered constructs.